Duration, Pattern of Breastfeeding and Postnatal Transmission of HIV: Pooled Analysis of Individual Data from West and South African Cohorts - Becquet, Renaud; Bland, Ruth; Leroy, Valériane; Rollins, Nigel C.; Ekouevi, Didier K.; Coutsoudis, Anna; Dabis, François; Coovadia, Hoosen M.; Salamon, Roger; Newell, Marie-Louise (PLOS ONE, 2009)
Background Both breastfeeding pattern and duration are associated with postnatal HIV acquisition; their relative contribution has not been reliably quantified. Methodology and Principal Findings Pooled data from 2 cohorts: in urban West Africa where breastfeeding cessation at 4 months was recommended but exclusive breastfeeding was rare (Ditrame Plus, DP); in rural South Africa where high rates of exclusive breastfeeding were achieved, but with longer duration (Vertical Transmission Study, VTS). 18-months HIV postnatal transmission (PT) was estimated by Kaplan-Meier in infants who were HIV negative, and assumed uninfected, at age >1 month. Censoring with (to assess impact of mode of breastfeeding) and without (to assess effect of breastfeeding duration) breastfeeding cessation considered as a competing event. Of 1195 breastfed infants, not HIV-infected perinatally, 38% DP and 83% VTS children were still breastfed at age 6 months. By age 3 months, 66% of VTS children were exclusively breastfed since birth and 55% of DP infants predominantly breastfed (breastmilk+water-based drinks). 18-month PT risk (95%CI) in VTS was double that in DP: 9% (7–11) and 5% (3–8), respectively (p = 0.03). However, once duration of breastfeeding was allowed for in a competing risk analysis assuming that all children would have been breastfed for 18-month, the estimated PT risk was 16% (8–28) in DP and 14% (10–18) in VTS (p = 0.32). 18-months PT risk was 3.9% (2.3–6.5) among infants breastfed for less than 6 months, and 8.7% (6.8–11.0) among children breastfed for more than 6 months; crude hazard ratio (HR): 2.1 (1.2–3.7), p = 0.02; adjusted HR 1.8 (0.9–3.4), p = 0.06. In individual analyses of PT rates for specific breastfeeding durations, risks among children exclusively breastfed were very similar to those in children predominantly breastfed for the same period. Children exposed to solid foods during the first 2 months of life were 2.9 (1.1–8.0) times more likely to be infected postnatally than children never exposed to solids this early (adjusted competing risk analysis, p = 0.04). Conclusions Breastfeeding duration is a major determinant of postnatal HIV transmission. The PT risk did not differ between exclusively and predominantly breastfed children; the negative effect of mixed breastfeeding with solids on PT were confirmed.